SQL jing dian shi li (di 2 ban) = SQL cookbook : second edition / = SQL cookbook : second edition - Molinaro, Anthony; De Graaf, Robert W. (O'Reilly Media, 2021)
Detailed summary in vernacular field.
Keywords: SQL (Computer program language); Query languages (Computer science); Database management; SQL (Langage de programmation); Langages d'interrogation; Bases de données; Gestion